Bamboo Fiber Composite Eco-Icebox for Food Storage Container - Balakrishnan, Mohana Ambigai; Nor Haslina Hashim (Progress in Engineering Application and Technology, 2022)
One of the common environmental problems is plastic disposal. Polystyrene trash, such as food storage containers and packaging were a major source of solid waste and pollution in  our country. Today, life would be impossible without polymer materials, both for practical and economical reasons. The objective of this research was to develop bamboo fiber composite eco-icebox (BFCEI) using bamboo fiber at 3%, 6% and 9%, clay soil and corn starch and to characterize the BFCEI  with regard to thermal conductivity, tensile strength and density. The characteristic was compared to polystyrene. Thermal conductivity was tested using Hot plate method and tensile strength data was extracted from Universal testing machine. Density was evaluated using weighing balance and ruler. Thermal conductivity of ratio 1, ratio 2 and 3 was 128.074 W/mk, 122.748 W/mk and 116.518 W/mk. The tensile strength shows the value was increasing parallel with bamboo fiber content. However, density of BFCEI increases simultaneously with increasing bamboo fiber content. Nevertheless, the result was compared with polystyrene data. The polystyrene presents better data compared to BFCEI in terms of thermal conductivity, tensile strength and density.